You are on page 1of 10

# Jacobians

Implicit Functions

## Jacobians of implicit functions

1) If x + y + z = u,y + z = uv,z=uvw
(,,)

## Prove that - (,,) =

Solution:Let f1=(x + y + z u) = 0
f2=(y + z - v) = 0
f3=(z - uvw) = 0

= |
(,,)

| = 1

( , , )
Also (,,) = |

| = -

(,,)

(,,)

( , , ) ( , , )

## But (,,) = (-1)3 [

(,,)

(,,)

Hence proved.

] =

Solved Problems

Jacobians

Implicit Functions

2) If u =

,v =

,w =

Solved Problems

where = + +
P.T.

(,,)
(,,)

= ()

## Solution:Given that (1- ) = , (1- ) = , (1- ) =

Let f1 = (1- ) = = (1- - - ) - = 0
f2 = (1- ) = = (1- - - ) - = 0
f3 = (1- ) = = (1- - - ) - = 0
(,,)
(,,)

( , , ) ( , , )

= (-1)3 [

(,,)

(,,)

] ---------(i)

( , , )

=
|

|
(,,)

+
( , , )
= -8xyz |
(,,)

By R1 + R2 + R3

|
+

Jacobians

Implicit Functions

Solved Problems

= -8xyz
+ + +
|

+ + + + + +
|
+

= -8xyz( + + + ) | +
|

+
By C2-C1 & C3-C2

= -8xyz( + + + ) |

= -8xyz( + + + )

-----------------(ii)

( )

( , , )
Also (,,) = |
|

( )

( )
= 8uvw(1-r2)3 -----------------(iii)
Putting (ii) & (iii) in (i),
( , , )
(,,)

3 (+ + + )

= (-1) .

( )

(+ + + )

( )

= ( )( )( ).

But = = =

And + + =

+ +

Jacobians

Implicit Functions

+ + +=
(,,)
(,,)

Solved Problems

+ =

= ( ) . . ( ) = ( )

## 3) If u,v,w are the roots of the equation

(-x)3 + (-y)3 + (-z)3 = 0 in ,find

(,,)
(,,)

## Solution:Simplifying the eqn. we get,

- 3(x+y+z) + 3( + + ) ( + + ) = 0
u+v+w=x+y+z
uv + vw + wu = + +

uvw = ( + + )
Let f1 = u + v + w - x - y z = 0
f2 = uv + vw + wu - = 0

f3 = uvw - ( + + ) = 0
(,,)
(,,)

( , , ) ( , , )

= (-1)3 [

( , , )
(,,)

(,,)

= |

(,,)

|

4

] ---------(i)

Jacobians

Implicit Functions

= -2|

## By C2-C1 & C3-C2

= -2|

( , , )
(,,)

= -2(y-x)(z-y) |

|
+

= -2(y-x)(z-y)[(z+y)-(y+x)]
= -2(x-y)(y-z)(z-x)
( , , )
(,,)

= | + +

-------------(ii)

+ |

## By C2-C1 & C3-C2

( , , )
(,,)

= | +

|
( ) ( )

= (u-v)(v-w)| + |

= (u-v)(v-w)(u-w)

---------------(iii)

= -(u-v)(v-w)(w-u)
Substituting the values from (ii)&(iii) in (i),
5

Solved Problems

Jacobians

(,,)
(,,)

Implicit Functions

()()()
()()()

4) If u = xyz , v = + + , w = x+y+z
(,,)

Find (,,)
ux = yz

uy = xz

uz = xy

vx = 2x

vy = 2y

vz = 2z

wx = 1

wy = 1

wz = 1

(,,)
(,,)
(,,)
(,,)

= | |

= ( )( )( + )

(,,)

=
(,,)

()()(+)

5) If u1 = f1(x1)
u2 = f2(x1 , x2)
u3 = f3(x1 , x2 , x3)
( , , )

P.T. ( , , ) =

. .

Solved Problems

Jacobians

Implicit Functions

(,,)

Hence or find

(,,)

Where x = cosu
y = cosv sinu
z = cosw sinv sinu

( , , )
( , , )

( , , )

( , , )

|
|

. .

Hence proved
(,,)

=
. .
(,,)

= (-sinu) (-sinv . sinu) (-sinw sinu .sinv)
= .

If x =

y = z =

u = .
v = .
w =
7

Solved Problems

Jacobians

(,,)

=
( )

Implicit Functions

Solved Problems

(,,) (,,)
(,,) (,,)

(,,)
(,,)

= | |
( )

= | |

= cos ( . . + . . ) +
( + )
( )

= cos . +
= ( + )
=

(,,)

( )

If u = xy + yz + xz
v = + +
w=x+y+z

Jacobians

Implicit Functions

Solved Problems

## 6) If the variables x,y,u,v are connected if the Relation

f1(x,y,u,v)=0
f2(x,y,u,v) = 0 then u,v are implicit function of x and y then
( )
( )

( )
}
(,)
( )
{ }
(,)

() {

If + + =
uv +xy = 0

( )

P.t. ( ) = +
(,,,)= + + = 0
(,,,)= + =
( )
( )

= |

= |

= 2( )
( )
( )

= |

( )
( )

| = ( + )

( )
( + )
( )

= ( +)

Jacobians

Implicit Functions

7) If + = +
+ = +
( )

P.T. ( ) =

()

(,,,)= + = 0
(,,,)= + = 0
( )
( ,)

= |

( )
( ,)

( , )
( ,)

| = ( )

= |
| =

= ( )

( )
()

()

10

Solved Problems